Wpływ polskiego komponentu Aegis Ashore na relacje z USA i NATO jako determinanta bezpieczeństwa międzynarodowego - Murat-Bors, Aleksandra (Polityka i Społeczeństwo, 2020)
The proliferation of nuclear weapons and ballistic missiles combined with the growing threat from „rogue states” are the premises leading to the inevitable development of the missile defence strategy. The Aegis Ashore component based in Poland aims to protect American allies and resources in the European region from the growing rocket threat. The program, which was also included in the NATO Ballistic Missile Defence, is undoubtedly of great importance for international security. The article contains a presentation of the nature and purpose of the BMDS and presents the impact that the project has on Poland’s relations with the United States and the NATO. It presents possible present and future implications for international security.